Trachea repair using an autologous pericardial patch combined with a 3D carbon fiber stent: A case report - Wang, Bin; Zhang, Zhe; Guo, Yuanwei; Yu, Fenglei (Frontiers in Surgery, 2023)
This study is the first to use an autologous pericardial patch combined with a 3D carbon fiber stent for the plastic repair of a large trachea defect. Radical surgery is the optimal therapy for primary malignant tracheal tumors. Tracheoplasty or repair is required to guarantee trachea integrity and normal ventilation function after tracheal tumor resection. Here, we present a case of plastic repair of the trachea using an autologous pericardial patch and a 3D custom-made carbon fiber stent. A 4 cm trachea defect was successfully repaired after resecting a malignant schwannoma. The postoperative ventilatory function was normal without obvious symptoms of discomfort. Fiberoptic bronchoscopy showed a smooth mucosal surface of the endotracheal wall and patency of the airway. CT scans performed 3 years after surgery showed no recurrence. Therefore, we can conclude that a 3D carbon fiber stent is feasible for abolishing patch floating and preventing tracheal stenosis.